Values and Career Interests of Mathematically Precocious Youth - Fox, Lynn H. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1973)
The major emphasis of this study is to identify and counsel seventh, eighth, and young ninth-grade students who are mathematically gifted. Such youngsters were identified as those scoring 600 or above on the mathematics section of the Scholastic Aptitude Test (SAT). This paper summarizes what has been learned about the career interests of mathematically precocious youth and how these measures have provided insights into (1) the nature of mathematical precocity, (2) the differences between the sexes in this respect, and (3) the success of various educational intervention procedures. Career interest were measured by a checklist of six categories of occupations and a questionnaire which asked the student to list his current career choices. The Allport-Vernon-Lindzey Study of Values was used to assess the values of the students. Results of the vocational interest study indicated that the majority of these students had strong interests in mathematical and scientific careers. The relationship of values to performance on the mathematics test was complex. The author elaborated on the findings. (Author/BW)
ERIC Note: Paper presented at the Annual Meeting of the American Psychological Association (81st, Montreal, Quebec, August 1973).
Educational level discussed: Junior High Schools.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Aspiration; Career Choice; Exceptional Child Research; Gifted; Junior High Schools; Mathematics Education; Sex Differences; Speeches; Values; Vocational Interests; Speeches/Meeting Papers